Uma contribuição crítica para o redesenho de cadeiras de rodas adaptadas para crianças e adolescentes com paralisia cerebral - Amorim, Brunna Michelle Paiva de (2009)
This work was aimed at making a critical analysis of the product wheelchair, both for using four different models, which were objects of study of the dissertation of Cláudia Regina Cabral Galvão, entitled Critical Analysis of the Mobility Products Seated a wheelchair - Used by Children and Adolescents with Cerebral Palsy in Natal / RN and other municipalities of Rio Grande do Norte . This product is considered an instrument in the social rehabilitation of great importance for people with physical disabilities. This study aims to position the issue and develop comments on technical up grading of certain models according to the needs of the user. Describes features of four models in search searched through catalogs in order to know its advantages and disadvantages of use. Were presented the definitions of ergonomics and ergonomic aspects to be considered on a design, the study of anthropometry and its recommendations. Discussions the methodology of project design in two parts: the first, on the structuring of design problem (formulation, analysis, synthesis and evaluation.) And the second on the project (design and development, implementation and evaluation and solution). With that review will include the possibilities for a new redesign of the wheelchair, based on forms of adaptation in order to achieve the target that was compressed by the average population studied. Seeks to that this project makes an improvement in quality of life of people in wheelchairs by including these people in society but also the improvement of rehabilitation